SUMBA TRIBAL CATCH MARRIAGE TRADITION IN THE PERSPECTIVE OF LEGAL PLURALISM - Adinda Agis Fitria Cahyani; Nadia Elvin Eka Azaria (JURNAL PANAH KEADILAN, 2024)
Kawin tangkap is a tradition originating from Sumba, East Nusa Tenggara with the Merapu faith. Kawin tangkap is a tradition of marriage without proposal by capturing and kidnapping a woman to marry. The purpose of this study is to determine the legal pluralism of the capture marriage tradition in Sumba. This type of study uses a qualitative type method with a legal pluralism approach. The results of this study show that kawin tangkap is a tradition commonly practiced in Sumba, but it violates national law, namely Article 328 of the Criminal Code on the crime of kidnapping, Article 6 paragraph 1 of Law Number 16 of 2019 concerning Marriage, and Article 10 Paragraph (1) of Law Number 12 of 2022 concerning Crimes of Sexual Violence.